2016
DOI: 10.1111/jicd.12245
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal regeneration in aggressive periodontitis patients: A systematic review of the literature

Abstract: The aim of the present study was to systematically review the existing literature on periodontal regenerative procedures in individuals affected by aggressive periodontitis (AgP). An electronic and manual search was performed using an ad hoc prepared search string. All types of study designs were considered acceptable for inclusion. Data about treated patients, baseline clinical parameters, type of surgery, and outcomes were extracted and recorded. A narrative evaluation of the results was performed. After the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 36 publications
2
16
2
2
Order By: Relevance
“…Clinical and radiographic improvements in the present study are in agreement with the conclusions of a systematic review showing that GTR may be successfully performed in patients affected by AgP [32]. Surprisingly, only two RCT studies (three articles) have been reported in the literature and none of the biomaterials used could be affiliated with better outcomes.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Clinical and radiographic improvements in the present study are in agreement with the conclusions of a systematic review showing that GTR may be successfully performed in patients affected by AgP [32]. Surprisingly, only two RCT studies (three articles) have been reported in the literature and none of the biomaterials used could be affiliated with better outcomes.…”
Section: Discussionsupporting
confidence: 81%
“…BMP2 is involved in all crucial osteogenic pathways: Wnt/β-catenin cascade, fibroblast growth factor-2 (FGF2), Hedgehog (Hh) signaling as well as in Smad and Notch signaling [30]. Translocation of gingival fibroblasts/GMSCs and PDPCs alters their behavior in response to periodontal ligament and bone mediators [31,32]. Manifold molecular interactions may guide the activation and subsequent differentiation of these cells towards an osteoblastic lineage.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, one recent controlled study reported superior bone regeneration following AC repair with non‐induced BMSC‐loaded HA scaffolds, compared to the gold standard, that is AB grafts (Khalifa & Nowair, ). Nevertheless, since the current pre‐clinical evidence from large‐animal models is also conflicting (Adamzyk et al., ; Corbella et al., ), no clear conclusions can be drawn regarding the benefits of osteogenic pre‐differentiation of MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Reconstruction of oral and maxillofacial bone deficiencies is often a clinical challenge. Ridge remodelling following tooth loss is the most common cause for alveolar bone deficiencies in the horizontal and/or vertical dimensions (Chiapasco & Casentini, ; Rocchietta, Ferrantino, & Simion, ), and in the posterior edentulous maxilla, this is further complicated by pneumatization of the maxillary sinus(es) (Corbella, Weinstein, Francetti, Taschieri, & Del Fabbro, ; Danesh‐Sani, Engebretson, & Janal, ). More challenging segmental defects, which include the inferior mandibular border, often result from trauma, tumour resection, or radiation‐related osteonecrosis (Chanchareonsook, Junker, Jongpaiboonkit, & Jansen, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, in patients with periodontitis, the number and function of intrinsic MSCs are often compromised 4,5 . Therefore, application of these methods is limited for periodontal regeneration 6 …”
mentioning
confidence: 99%